Requirements Engineering: Foundation for Software Quality: 24th International Working Conference, REFSQ 2018, Utrecht, The Netherlands, March 19-22, 2018, Proceedings - Kamsties, Erik; Horkoff, Jennifer; Dalpiaz, Fabiano (Lecture notes in computer science, 2018)
This book constitutes the proceedings of the 24th International Working Conference on Requirements Engineering - Foundation for Software Quality, REFSQ 2018, held in Utrecht, The Netherlands, in March 2018. The 23 full and 2 invited talks papers presented in this volume were carefully reviewed and selected from 57 submissions. The papers were organized in topical sections named: RE in Industrial Practice; NLP in Theory and Practice; Empirical Insights into Traceability; Taming Ambiguity; Large-Scale RE; Quality Requirements; User and Job Stories; Requirements Alignment; RE Previews and Visions; Big Data; Mindmapping and Requirements Modeling